Malaysian government officials induced in public procurement fraud through the lens of fraud diamond analysis - Norziaton Ismail Khan,; Hamzah Bakar, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Public procurement fraud by government officials has resulted in a sizeable loss of public funds, subsequently smearing a bad reputation of a local institution in the eyes of the public. The appropriate parties and the government as the trustees of public funds should tackle the presence of the propelling elements in driving government officials to engage in fraudulent behaviour. Besides, they should also ensure to eradicate, or at the least, prevent the problem from worsening. Therefore, this study attempted to determine the effect of fraud diamond analysis on public procurement fraud. Fraud Diamond is measured by perceived pressure, rationalisation, opportunity, and capability. The researchers gathered primary data through a survey using 165 questionnaires distributed to the government officials of all 27 ministries at the Federal level. Several statistical techniques such as descriptive statistics, correlation, and regression analysis were used to analyse the data from the survey. Four hypotheses were developed, and the findings showed that perceived pressure, perceived rationalisation, and perceived capability significantly influenced public procurement fraud by government officials, hence being accepted. In contrast, the perceived opportunity was rejected. This study aids academics, legislators, lawmakers, sociologists, psychologists, and those engaged in financial crime scene investigation, such as authorities and regulators, to understand the reason behind the fraudulent behaviour of fraudsters.